Use of urine volatile organic compounds to discriminate tuberculosis patients from healthy subjects - Banday, Khalid Muzaffar; Pasikanti, Kishore Kumar; Chan, Eric Chun Yong; Singla, Rupak; Rao, Kanury Venkata Subba; Chauhan, Virander Singh; Nanda, Ranjan Kumar (Analytical chemistry (Washington), 2011)
Development of noninvasive methods for tuberculosis (TB) diagnosis, with the potential to be administered in field situations, remains as an unmet challenge. A wide array of molecules are present in urine and reflect the pathophysiological condition of a subject. With infection, an alteration in the molecular constituents is anticipated, characterization of which may form a basis for TB diagnosis. In the present study volatile organic compounds (VOCs) in human urine derived from TB patients and healthy controls were identified and quantified using headspace gas chromatography/mass spectrometry (GC/MS). We found significant (p < 0.05) increase in the abundance of o-xylene (6.37) and isopropyl acetate (2.07) and decreased level of 3-pentanol (0.59), dimethylstyrene (0.37), and cymol (0.42) in TB patients compared to controls. These markers could discriminate TB from healthy controls and related diseases like lung cancer and chronic obstructive pulmonary disorder. This study suggests a possibility of using urinary VOCs for the diagnosis of human TB.